1999
DOI: 10.1053/cp.1999.v66.a102203
|View full text |Cite
|
Sign up to set email alerts
|

Flavin monooxygenase 3 (FMO3) polymorphism in a white population: Allele frequencies, mutation linkage, and functional effects on clozapine and caffeine metabolism*1

Abstract: There are several genetic polymorphisms for the FMO3 enzyme. The effects on the metabolism of caffeine or clozapine could not be shown, indicating that the mutations have only minor functional effects or that substrate affinity is too low to be clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…By contrast, the L360 P polymorphism has been shown to increase the catalytic efficiency of FMO3 [30,31]. In addition, Sachse and colleagues, using a population-based analysis model, did not establish a clear link between certain FMO3 polymorphisms and the metabolism of clozapine or caffeine, suggesting that the mutations examined have only minor functional effects, or that substrate affinity may be too low to be clinically relevant [17]. Of the several variants, the E158K, E308G and V257M polymorphisms have been shown to have a relatively high population distribution [27].…”
Section: Effects Of Fmo3 Polymorphisms On Substrate Metabolism In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, the L360 P polymorphism has been shown to increase the catalytic efficiency of FMO3 [30,31]. In addition, Sachse and colleagues, using a population-based analysis model, did not establish a clear link between certain FMO3 polymorphisms and the metabolism of clozapine or caffeine, suggesting that the mutations examined have only minor functional effects, or that substrate affinity may be too low to be clinically relevant [17]. Of the several variants, the E158K, E308G and V257M polymorphisms have been shown to have a relatively high population distribution [27].…”
Section: Effects Of Fmo3 Polymorphisms On Substrate Metabolism In Vitromentioning
confidence: 99%
“…Ryu and colleagues showed that overproduction of nitric oxide in the liver may suppress FMO3 activity directly via reversible S-nitrosylation [37]. N-oxygenation of nicotine [38], clozapine [17] and the histamine 2 receptor (H 2 ) blockers, cimetidine [39] and ranitidine [40], have all been used to phenotype patient populations with FMO3 variants.…”
Section: In Vivo Effects Of Fmo3 Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europeans and Asians the two most common SNPs, g.15167G>A(E158K) [15,42] and g.21443A>G(E308G) [16], are often linked, occurring on the same chromosome [43][44][45][46]. The compound variant (E158K/E308G) can result in a reduction of enzyme activity, the extent of which depends on the substrate [2][3][4]38,40,41,46].…”
Section: Fmo3mentioning
confidence: 99%
“…Oxygenation of (S)-nicotine (Park et al, 1993), TMA (Treacy et al, 1998), cimetidine (Cashman et al, 1993a), clozapine (Sachse et al, 1999), and ranitidine have been used to phenotype various populations for human FMO3 activity. All five materials have been shown to be relatively selective probes of human FMO3 activity in vitro.…”
Section: Interindividual Variability Of Human Fmo3 Functional Activitmentioning
confidence: 99%